Cardiac and testicular alterations induced by acute exposure to titanium dioxide nanoparticles: Histopathological study - Amin Al‐Doaiss; Bashir Jarrar; Ali Shati; Mohammed Al‐Kahtani; Mohammad Alfaifi (IET Nanobiotechnology)
Abstract Titanium dioxide nanoparticles (TiO2 NPs) have novel application and are used in many household application, nanomedicine, agriculture, industries and pharmaceutical products. These applications may be accompanied with potential risk in human health and the ecosystems. The current study was carried out to find out the acute damage that might be induced by TiO2 NPs in the heart and testis. Three groups of Wistar albino rats (Rattus norvegicus) were subjected to a single dose TiO2 NPs (126, 252, 378 mg/kg bw). Cardiac and testicular biopsies from each animal under study were handled for histological and histochemical examination. Rats exposed to TiO2 NPs demonstrated the following cardiac alterations: myofibres wavy appearance, myofibre disarray, partial cross striation, cardiomyocytes hydropic degeneration together with vacuolation and nuclear alterations. Moreover, acute exposure to TiO2 NPs induced the following testicular alterations: spermatocytes degeneration, spermatids sloughing and interstitial edema. The presented cardiac and testicular alterations were dose dependent. From the findings of the present study, it might be concluded that TiO2 nanomaterials are capable of inducing acute cardiac and testicular damage that is dose dependent and could adversely affect the function of the vital organs.